The Tourist Experience of Heritage Urban Spaces: Valletta as a Case Study. Issue 4 (3rd July 2020) - Ebejer, John; Smith, Andrew; Stevenson, Nancy; Maitland, Robert
ABSTRACT: This article provides an understanding of how tourists experience heritage urban spaces by investigating features that influence tourist experiences most. It is framed within urban design literature which refers to three elements of urban space namely physical setting (or form), activity, and meaning. These elements are used to explore how urban spaces are experienced by tourists. Its findings are derived from an in-depth qualitative analysis of interviews with tourists to Valletta, Malta. The research suggests that the intrinsic qualities of the space are relevant to the tourist experience but what is even more relevant are the interactions of the tourist with different elements within that space, namely interactions with surroundings, interactions with others, and interactions with self/meaning. Within this broad conceptual model, the research identifies important sub-themes. Some of these reinforce the findings of existing work on tourist experiences, but others are often under-estimated or neglected.